The Precambrian geology of El Cristo, southern Tandilia Region, Argentina - Dalla Salda, Luis Hugo (1981)
Metamorphic and granitoid rocks of the El Cristo area, southern part of Tandilia Range, are considered in terms of structural, lithological and geochronological data. The abovementioned area was affected before 2000 m. y. by a first tectono-thermal event that was followed by a second episode of intense SW-NE folding. The latter accompanied or followed by a metamorphism of almandine grade and strong synkinematic to latekinematic granitization during the span 1800-1520 m. y. Succeeding episodes of metamorphism and deformation were less intense and culminated in the local development of a 900 m. y. granite, chloritization and some brittle deformation.